Pengembangan Media Spedomatik pada Pemahaman Konsep Nilai Tempat di Sekolah Dasar - Dwi Setyawan, Dedy (Jurnal Didaktika Pendidikan Dasar, 2020)
The development of Spedomatik media has the aim of strengthening the understanding of mathematical concepts and improving student learning outcomes. This innovation was developed by applying the Research and Development method. The results show that the percentage of student learning outcomes has increased, from before the use of Spedomatik on average only 54.44% then increased when the trial 1 became 52.22% and increased in the second trial to 75.55%. Conclusions obtained for the achievement of improvements that occur due to the use of Spedomatik media, where the activeness of students in manipulating Spedomatik is a stage in understanding mathematical concepts.